Pelaksanaan Pembiasaan Kegiatan Tadarus Qur’an terhadap Kedisiplinan Belajar Siswa SMP Negeri 10 Palembang - Astuti, Mardiah; Lestari, Indah; Muzdalifah, Muzdalifah; Nurmalina, Nurmalina; Apriliani, Selvy (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the process of implementing the practice of tadarus Qur’an in fostering learning discipline among students at SMP Negeri 10 Palembang. The research employs a case study design and qualitative methodology. Data collection was conducted through in-depth interviews, observations, and documentation involving 70 students who regularly participated in tadarus activities, along with three teachers who assisted in the implementation. The data analysis technique employed involved stages of data collection, data presentation, verification, and conclusion drawing. The findings of the study highlight the significance of tadarus Al-Qur'an activities in enhancing students' learning discipline, as evidenced by increased attentiveness during class, consistency in completing assignments, and punctuality. Daily recitation of the Qur'an helps students develop good time management skills and greater focus on academic work. Students who cultivate this habit are also more likely to grow into disciplined and responsible adults. Furthermore, the study revealed that teacher support in implementing tadarus has a significant impact on how effectively this practice improves student discipline. Regular tadarus Al-Qur'an activities can be further developed to better support students' academic discipline